A Study on Factors Affecting Career Advancement in Organization at Klang Valley - Mei Ting, Wong; Poon Wai Chuen, Eugene; Binti Ahmad, Noraini (International Journal of Psychosocial Rehabilitation, 2020)
Career advancement is seen as a tool for organisation to match employees’ career aspiration to the organisations’ goal and objective in order to maintain satisfaction and commitment. The aim of this study is to determine factors influencing career advancement in organization at Klang Valley. Questionnaire examining the relationship between the dependent such as career advancement and independent variable such as relationship between immediate supervisor, colleague, professionalism, career management skills, proactive career management. A total of 160 responses were obtain from employees in Klang Valley. The results revealed that the variables had a significant impact on career advancement.